Stabilization of the β-hairpin in Mason-Pfizer monkey virus capsid protein- a critical step for infectivity - Obr, Martin; Hadravová, Romana; DoleŽal, Michal; KříŽová, Ivana; Papoušková, Veronika; Zídek, Lukáš; Hrabal, Richard; Ruml, Tomáš; Rumlová, Michaela (Retrovirology, 2014)
BACKGROUND: Formation of a mature core is a crucial event for infectivity of retroviruses such as Mason-Pfizer monkey virus (M-PMV). The process is triggered by proteolytic cleavage of the polyprotein precursor Gag, which releases matrix, capsid (CA), and nucleocapsid proteins. Once released, CA assembles to form a mature core - a hexameric lattice protein shell that protects retroviral genomic RNA. Subtle conformational changes within CA induce the transition from the immature lattice to the mature lattice. Upon release from the precursor, the initially unstructured N-terminus of CA is refolded to form a β-hairpin stabilized by a salt bridge between the N-terminal proline and conserved aspartate. Although the crucial role of the β-hairpin in the mature core assembly has been confirmed, its precise structural function remains poorly understood. RESULTS: Based on a previous NMR analysis of the N-terminal part of M-PMV CA, which suggested the role of additional interactions besides the proline-aspartate salt bridge in stabilization of the β-hairpin, we introduced a series of mutations into the CA sequence. The effect of the mutations on virus assembly and infectivity was analyzed. In addition, the structural consequences of selected mutations were determined by NMR spectroscopy. We identified a network of interactions critical for proper formation of the M-PMV core. This network involves residue R14, located in the N-terminal β-hairpin; residue W52 in the loop connecting helices 2 and 3; and residues Q113, Q115, and Y116 in helix 5. CONCLUSION: Combining functional and structural analyses, we identified a network of supportive interactions that stabilize the β-hairpin in mature M-PMV CA.
Keywords: mutace; Animals; virion; buněčné linie; HEK293 Cells; sekvence aminokyselin; Virion; Capsid Proteins; lidé; Molecular Sequence Data; AIDS opičí; Mutation; Amino Acid Sequence; HEK293 buňky; Cell Line; Virus Assembly; molekulární sekvence - údaje; sestavení viru; Protein Structure, Secondary; Mason-Pfizer monkey virus; Masonův-Pfizerův opičí virus; virové plášťové proteiny; sekundární struktura proteinů; zvířata; Simian Acquired Immunodeficiency Syndrome; Humans